Prevalence, Characteristics, and One-Year Follow-Up of Congenital Cytomegalovirus Infection in Isfahan City, Iran - Karimian, Pegah; Yaghini, Omid; Nasr Azadani, Hossein; Mohammadizadeh, Majid; Arabzadeh, Seyed Ali Mohammad; Adibi, Atosa; Rahimi, Hamid (Interdisciplinary Perspectives on Infectious Diseases, 2016)
Introduction. Need of neonatal screening for Cytomegalovirus (CMV) infection is under debate, in part because of limited data on importance of the disease regarding the prevalence of congenital CMV (cCMV) infection and associated morbidity and mortality. We aimed to evaluate the prevalence and prognosis of cCMV infection in Iran, where there is high maternal seroprevalence of CMV. Methodology. This prospective study was conducted in Isfahan city, Iran, from 2014 to 2016. CMV was investigated in urine specimens by using the real-time polymerase chain reaction (RT-PCR) method. CMV-infected infants were examined for clinical and laboratory findings attributed to CMV infection and followed up for one year. Results. Among 1617 studied neonates, eight (0.49%) were positive for CMV infection. CMV-infected neonates were more likely to be preterm than noninfected ones (25% versus 4.5%, p=0.0508), and they had lower birth weight. Three out of the eight CMV-infected neonates had transient symptoms at birth. At follow-up, one case had mild hearing loss. Most patients had impaired growth during the one-year follow-up. Conclusions. The primary object of this study was determination of prevalence of cCMV infection in Iran as a developing country, which was at the lower range compared with other such countries. cCMV infection may result in short-term impairment in growth.